The Big Five personality traits and theory of planned behavior in physical education students - Li, Yun; Ruzicka, Michal (Quality in Sport, 2022)
Purpose: This study aimed to test the correlation between the Big Five personality traits and the theory of planned behavior in Chinese physical education students. Design/methodology/approach: This is a cross sectional study which used the Big Five Inventory-44 and the Physical Educator’s Intention Toward Teaching Individuals with Disabilities III. Using a large number of randomly selected samples, a total of N =2305 physical education students (782 females and 1523 males, M age = 20.12, SD = 1.47) were purposely selected from 10 normal or comprehensive universities located in Eastern, Central and Western China. Findings: Our findings showed that the big five personality traits and theory of planned behavior are closely linked in physical education students. Future intervention experiments can focus on the impact of the big five personality traits on the TPB, to improve the mental health and academic performance of physical education students. Research and practical limitations/implications: First, the research method of this study is single, and subsequent studies can add mediator or moderator variables. Second, because this study is a cross-sectional study, it fails to explore the causal relationship between the Big Five personality traits and the various dimensions of the planned behavior theory of physical education for normal students. Originality/value: This study explored the relationship of the Big Five personality traits with intention, attitude toward the behavior, and subjective norms of physical education students, within the theory of planned behavior. It suggests ways for educators, counselors, and coaches to promote the physical and mental development of physical education students.